An Anglo-European Perspective on Industrial Relations Research - Hyman, Richard (Arbetsmarknad & Arbetsliv, 2018)
In this paper I review approaches to industrial relations research in Britain and in continental western Europe. My aim is to explore the diversity of traditions towards the analysis of the world of work, not only within Europe but also between Britain and the USA. My core argument differs in important respects from that of Bruce Kaufman: if the field of ‘traditional’ industrial relations scholarship is in decline and disarray in America, the situation in Europe is very different: recent years have seen moves towards a fruitful synthesis of the diversity of understandings of our field of study.